Ponto de inflex??o do duplo produto como m??todo alternativo para determina????o do limiar ventilat??rio e de lactato e associa????o com indicadores de desempenho - Silva, Caio Victor de Sousa (2016)
The validity of the double product (DP) response to estimate the anaerobic threshold (AT), an alternative and less costly method has not been tested in patients with type 2 diabetes (T2D). Therefore, the objective of this study is test the reliability of AT identification by the double product breakpoint (DPBP) in T2D. Nine subjects with type 2 diabetes (T2D = 9) and ten non-diabetic (ND = 10) underwent an incremental test on a cycle ergometer. Heart rate (HR), blood pressure (BP) and exhaled gases were measured at the end of each stage. The ventilatory threshold (VT), lactate threshold (LT) and DPBP were considered an exercise intensity below which a disproportional increase of ventilation, [LAC] and DP, respectively, was observed in relation to linear increase in workload. No differences were identified between the workload, HR, and oxygen consumption (VO2) corresponding to the AT identified by VT, LT and DPBP. Further, for the T2D group was identified a high and significant level of reliability between DPBP and VT for workload (ICC = 0.84), FC (ICC = 0.71) and VO2 (ICC = 0.83) and between DPBP and LT for workload (ICC = 0.79) and FC (ICC = 0.82). Similar reliability was identified for the ND group between DPBP and VT for workload (ICC = 0.92), HR (ICC = 0.88) and VO2 (ICC = 0.84) and between DPBP and LT for workload (ICC = 0.70). It concludes that the DPBP is reliable to estimate the AT and it is highly associated with VT and LT in T2D and ND individuals.